2002
DOI: 10.1038/emm.2002.44
|View full text |Cite
|
Sign up to set email alerts
|

Human FEN-1 can process the 5'-flap DNA of CTG/CAG triplet repeat derived from human genetic diseases by length and sequence dependent manner

Abstract: Trinucleotide repeat (TNR) instability can cause a variety of human genetic diseases including myotonic dystrophy and Huntington's disease. Recent genetic data show that instability of the CAG/CTG repeat DNA is dependent on its length and replication origin. In yeast, the RAD27 (human FEN-1 homologue) null mutant has a high expansion frequency at the TNR loci. We demonstrate here that FEN-1 processes the 5'-flap DNA of CTG/CAG repeats, which is dependent on the length in vitro. FEN-1 protein can cleave the 5'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 15 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…1A). Others have reported previously that hFEN1 is somewhat less active on flaps containing longer CTG repeats (11 or more repeats), consistent with the possibility that activity depends upon repeat length (27). Its flap endonuclease activity predominated on the unstructured flap substrate, whereas 5Ј-excision predominated on the substrate containing a (CTG) 8 repeat within the flap (Fig.…”
Section: Hfen1 5ј-flap Cleavage Is Impaired By Ctg or Cgg Repeats-supporting
confidence: 77%
“…1A). Others have reported previously that hFEN1 is somewhat less active on flaps containing longer CTG repeats (11 or more repeats), consistent with the possibility that activity depends upon repeat length (27). Its flap endonuclease activity predominated on the unstructured flap substrate, whereas 5Ј-excision predominated on the substrate containing a (CTG) 8 repeat within the flap (Fig.…”
Section: Hfen1 5ј-flap Cleavage Is Impaired By Ctg or Cgg Repeats-supporting
confidence: 77%
“…Subsequently, further studies suggested that Okazaki fragment initiation and processing at sequences consisting of expanded triplet repeats might account for their instability (Cleary et al, 2002;Mirkin and Smirnova, 2002). In support of this model, the flap endonuclease (FEN-1) has been shown to cause CAG repeat instability when hemizygous in mice and when absent in yeast (Lee and Park, 2002;Spiro and McMurray, 2003). As mutations in mismatch repair genes cause expansions and contractions of normal length dinucleotide and trinucleotide repeats in yeast, mice, and humans (Aaltonen et al, 1993;Peltomaki et al, 1993;Strand et al, 1993;de Wind et al, 1998), a role for mismatch repair enzymes in expanded triplet repeat instability has also been examined.…”
Section: Introductionmentioning
confidence: 94%
“…However, because of the singlestranded nature of the Okazaki fragments on the lagging strand, both expansions and deletions can occur depending on the stability of the hairpin structures formed by these repeats. The aberrant processing of the Okazaki fragments involving FEN-1 and DNA ligase has also been hypothesized to play an important role in generating genetic instabilities (21,(113)(114)(115)(116)(117)(118).…”
Section: Chemical Probe Determinations-d(cagg)mentioning
confidence: 99%